Recurrent Peptic Ulcer Perforation: A Case Report - Al Abri, MD, Maather; Al Mahruqi, MD, Ghaitha; Al Qadhi, FRCSC, Hani (International Journal of Innovative Research in Medical Science, 2022)
Background: Refractory peptic ulcers are ulcers in the stomach or duodenum that do not heal after eight to twelve weeks of medical/surgical treatment or those that are associated with complications despite medical tssreatment. We herein present a case of a 44 year old man with a recurrent perforated duodenal ulcer requiring emergent surgical intervention.